Identification of risk factors for 1-year mortality among critically ill older adults with hip fractures surgery: A single medical center retrospective study - Luo, Taijun; Zhang, Juxia; Zhou, Haibin; Xu, Tao; Zhang, Wenchao; Wang, Geng (Frontiers in Surgery, 2022)
AIM: The aim of this study is to examine potential risk factors for 1-year mortality after hip fracture surgery. METHODS: We reviewed 591 elderly and critically ill patients who underwent hip surgery at our institution from January 2018 to April 2021 retrospectively. The baseline demographic, clinical data and 1-year survival status in both groups were collected through the medical record system and follow-up phone calls. Patients were divided into survival group and death group according to the survival status within the first postoperative year. RESULTS: According to the results from 1year follow-up, 117 cases were classified into the death group while 474 cases were in the survival group, and it was calculated that the 1-year mortality rate of elderly and critically ill patients with hip fracture was 19.8% (117/591) in our hospital. The identified risk factors for 1-year mortality were advanced age (HR:1.04, 95%:1.01- 1.06), preoperative arrhythmia (HR:4E3 1.95, 95%: 1.26 - 2.70), high level of NLR (HR:1.03, 95%:1.01 - 1.06), respiratory failure (HR: 2.63, 95%:1.32 - 5.23) and acute cardiovascular events (HR: 1.65, 95%:1.05 - 2.59). CONCLUSION: Advanced age, preoperative comorbid arrhythmias, preoperative high level of NLR, respiratory failure and acute cardiovascular events postoperatively were independently associated with increased risk of 1-year mortality rate of critically ill elderly patients with hip fracture. Laboratory tests such as high level of NLR preoperative can be used as important indicators to determine the prognosis of patients.